Realising decolonising spaces: relational accountability in research events. (March 2023) - Jones, Tod; Dowling, Carol; Porter, Libby; Kickett-Tucker, Cheryl; Cox, Shaphan
Research events are important places where disciplinary structures and norms are reproduced and challenged. This article uses the authors' experiences organising a geography research event on decolonising settler cities on Wadjuk Nyungar Country in Perth, Western Australia, to interrogate the transformations that a decolonising ethic demands. Learning with the Indigenous research method of yarning as a decolonising practice, we document and reflect on the persistence a decolonising ethic requires. This project concretely revealed the interconnection between transformation at the micro-level—event conceptualisation, design, placement, and conduct—and building challenges to settler-colonial structures and institutions. We conclude by interrogating the structural barriers for multi-epistemic engagement and learning and propose three principles for non-Indigenous researchers to more fully understand the invitation of being in a relationship with what has always been here: Indigenous sovereignties of law, place, and knowledge.